Development of an ultra-high vacuum system for a cold atom physics rack in space. (August 2021) - Liu, Qian; Xie, Yu; Li, Lin; Xiang, Jingfeng; Wang, Wenli; Qu, Qiuzhi; Fang, Su; Wang, Bin; Lü, Desheng; Liu, Liang
Abstract: We present the design and testing of the ultra-high vacuum (UHV) system, which is a key apparatus for the Cold Atom Physics Rack (CAPR) operated on the Chinese Space Station that allows study of ultracold atoms in microgravity. The simulation of the gas flow and experimental tests show that our UHV has a pressure of 3.4 × 10 − 9 Pa in the science chamber, two orders of magnitude lower than that of the 2D magneto-optical trap (2D-MOT) chamber. Moreover, we demonstrate that the system can not only self-sustain an equilibrium pressure for more than 1 month without power but also restore the desired pressure in the interaction zone. The loss dynamics of the trapped atoms are also measured to assess the performance of the UHV system. Highlights: Ultra-high vacuum systems for space applications. Design of an ultra-high vacuum system for ultracold atomic physics. Simulation of the ultra-high vacuum systems. Verification of the ultra-high vacuum systems.